2017
DOI: 10.3390/nu9050436
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Mechanism Involved in Pomegranate-Mediated Prevention of Breast Cancer: the Role of NF-κB and Nrf2 Signaling Pathways

Abstract: Pomegranate (Punica granatum L.), a nutrient-rich unique fruit, has been used for centuries for the prevention and treatment of various inflammation-driven diseases. Based on our previous study, a characterized pomegranate emulsion (PE) exhibited a striking inhibition of dimethylbenz(a)anthracene (DMBA)-initiated rat mammary tumorigenesis via antiproliferative and apoptosis-inducing mechanisms. The objective of the present work is to investigate the anti-inflammatory mechanism of action of PE during DMBA rat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 88 publications
0
41
0
Order By: Relevance
“…NRF2, a transcription factor which is associated with Keap1, is regarded as a key role in guarding cells against oxidative stress . It binds the antioxidant DNA response element (ARE) to activate critical cytoprotective defense, and NRF2 deletion increased treatment sensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…NRF2, a transcription factor which is associated with Keap1, is regarded as a key role in guarding cells against oxidative stress . It binds the antioxidant DNA response element (ARE) to activate critical cytoprotective defense, and NRF2 deletion increased treatment sensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, multiple lines of evidence have shown the anti‐inflammatory properties of pomegranate extracts. Mandal et al . reported that 0.2–5.0 g kg −1 pomegranate extracts show anti‐inflammatory effects by inhibiting the translocation of NF‐κB from the cytosol to the nucleus in a dose‐dependent manner in vivo.…”
Section: Mechanism Analysis Of Lipid Metabolism Regulated By Pomegranatementioning
confidence: 99%
“…[104] Furthermore, multiple lines of evidence have shown the anti-inflammatory properties of pomegranate extracts. Mandal et al [105] reported that 0.2-5.0 g kg −1 pomegranate extracts show anti-inflammatory effects by inhibiting the translocation of NF-κB from the cytosol to the nucleus in a dose-dependent manner in vivo. Harzallah et al [67] showed that pomegranate flower (250 mg kg −1 day −1 ), peel (250 mg kg −1 day −1 ) and seed oil (2 mL kg −1 day −1 ) are capable of reducing the plasma levels of interleukin-6 (IL-6) and TNF-α in HFD-induced obese mice and that pomegranate flower increases the level of the anti-inflammatory cytokine interleukin-10 (IL-10).…”
Section: Mechanism Analysis Of Lipid Metabolism Regulated By Pomegranatementioning
confidence: 99%
“…versicolor , A. ochraceus , A. niger , Trichoderma viride , Penicillium funiculosum , P. ochrochloron , P. verrucosum ) and antiradical effects (DPPH • [2,2‐diphenyl‐1‐picrylhydrazyl] and ABTS • [2,2′‐azino‐bis‐(3‐ethylbenzothiazoline‐6‐sulfonic acid]; and anti‐osteoporotic and anti‐obesity properties on ovariectomized rats . Pomegranate increased the prostate‐specific antigen in patients with prostate cancer, had antiproliferative effects on cervical and prostate cancer cells, and rat breast cancer tumors and decreased the expression of heat shock protein 90, cyclooxygenase‐2 and monoamine oxidase‐A enzymes, which are key enzymes in inflammatory and neurotransmitter processes, respectively . Proapoptotic properties have been reported in leukemia cell lines (two lymphoid and two myeloid cell lines) .…”
Section: Introductionmentioning
confidence: 99%
“…8 Pomegranate increased the prostate-specific antigen in patients with prostate cancer, 9 on cervical and prostate cancer cells, and rat breast cancer tumors and decreased the expression of heat shock protein 90, cyclooxygenase-2 and monoamine oxidase-A enzymes, which are key enzymes in inflammatory and neurotransmitter processes, respectively. 10,11 Proapoptotic properties have been reported in leukemia cell lines (two lymphoid and two myeloid cell lines). 12 However, the most studied aspect is the antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%